Using a Holistic Modeling Approach to Simulate Mud‐Induced Periodic Stratification in Hyper‐Turbid Estuaries - J. Schmidt; A. Malcherek (Geophysical Research Letters)
Abstract This study focuses on a holistic modeling approach, in which water, fluid mud, and immobile mud are all calculated by only one set of equations. To integrate the immobile mud into this concept, a holistic transport equation including sediment transport and consolidation is developed. In some estuaries, extensive deepening and dredging resulted in tidal deformation and sediment import to such extent, that hyper‐turbid conditions developed. Recent measurements from the Ems estuary show that the locations of interfaces between water, fluid mud, and consolidated mud vary during a tidal cycle. Conditions are varying from fully mixed to stably stratified. As a suitable case study for the holistic model, a 1D vertical numerical simulation of the Ems has been set up, which is able to qualitatively reproduce the observed vertical velocity, concentration, and velocity shear profile. The simulation shows mud‐induced periodic stratification.